Synthesis, cytotoxic evaluation, and binding studies of novel sulphamethoxazole-based cyanoacrylamides as potential antitumor agents - Fatma G. Mohamed; Mohamed A. Ragheb; Ahmed H.M. Elwahy; Hadeer M. Diab; Marwan Emara; Mostafa E. Salem; Ibrahim O. Althobaiti; Ismail A. Abdelhamid (Results in Chemistry)
Molecular hybridization has become a leading and highly effective method for creating new anticancer chemotherapeutic drugs. In this endeavor, new cyanoacrylamides with derivatives of sulphamethoxazole (5a-5f) have been created and verified utilizing different spectral instruments. The SRB assay evaluated the cytotoxic activities of the tested compounds against 16Lu, a human normal cell, and several human cancer cells (HCT116, MCF7, and HepG2). Among all derivatives, 5a and 5b had the most potent cytotoxicity effect against HepG2 cells with IC50 = 11.06 ± 0.829 and 18.836 ± 2.68 μg/ml, respectively. The binding affinities of 5a and 5b with DNA and BSA were studied using different spectroscopic techniques. Furthermore, molecular docking for 5a and 5b was performed to confirm the experimental results and anticipate their binding capabilities toward DNA and BSA. Thus, this work introduces promising antitumor lead compounds, encouraging further activity enhancement and therapeutic development studies.